Effects of polystyrene microparticles, gadolinium salts and their mixtures to soil annelid studied in agar exposure medium - Hrdá, Kateřina; Konopáčová, Eliška; Knotek, Petr (University of Pardubice, 2021)
Environmental risk assessment requires to conduct standardized ecotoxicological bioassays that can, at least, partially imitate realistic exposure scenarios. However, the study of the ecotoxic effects of particulate materials is complicated mainly by the fact that particles have different physical-chemical properties resulting in different distribution in the test medium in comparison with soluble pollutants. Therefore, in this study, the agar-based experimental system has been used to examine the toxicity of plastic microparticles to the soil decomposer Enchytraeus crypticus. Furthermore, of interest was the effect of the presence of plastic particles on the toxicity of gadolinium salts whose harmfulness to soil organisms is less known. The agar-based exposure medium enabled the consistent dispersion and agglomeration state of particles during the experiments under stable conditions with the characterization of the particles directly in the exposure medium. Gadolinium was tested in the form of Gd(NO3)3 and two contrast agents - Dotarem® (Acidum gadotericum) and MultiHance® (Dimeglumi gadobenas). The polystyrene particles (65–497 μm) were prepared by cryogenic grinding of coffee cup lids. The estimated 96h LC50 for gadolinium was higher than 1 g kg−1 of agar, which suggests a relatively low acute toxicity to E. crypticus. The polystyrene particles exhibited no toxicity to E. crypticus even at very high concentrations (1–25 g kg−1 of agar) after 10 days of exposure. The survival rate, the content of malondialdehyde in the biomass, or biomass production E. crypticus were not affected after 10-day of exposure to three different concentrations of Gd in the presence of particles.
Keywords: ecotoxicity; microparticles; gadolinium; contrast agent; agar